Climate Change, Security Risks, and Violent Conflicts Essays from Integrated Climate Research in Hamburg - Alcón, Francisco; Brzoska, Michael; Scheffran, Jürgen (Hamburg University Press, 2020)
Research on security-related aspects of climate change is an important element of climate change impact assessments. Hamburg has become a globally recognized center of pertinent analysis of the climate-conflict-nexus. The essays in this collection present a sample of the research conducted from 2009 to 2018 within an interdisciplinary cooperation of experts from Universität Hamburg and other institutions in Hamburg related to the research group "Climate Change and Security" (CLISEC). This collection of critical assessments covers a broad understanding of security, ranging from the question of climate change as a cause of violent conflict to conditions of human security in the Anthropocene. The in-depth analyses utilize a wide array of methodological approaches, from agent-based modeling to discourse analysis.